Wear Properties of Fe-Cr-C and B4C Powder Coating on AISI 316 Stainless Steel Analyzed by the Taguchi Method - Gur, Ali Kaya; Ozay, Cetin; Orhan, Ayhan; Buytoz, Soner; Caligulu, Ugur; Yigitturk, Necmettin (Carl Hanser Verlag, 2014)
In this study, the plasma arc welded cladding of FeCrC and B4C powder mixtures alloyed with 70 wt.-% Cr on the surface of AISI 316 stainless steel was investigated. Application of the Taguchi method revealed respective effects on the abrasive wear resistance of the cladding layer on the stainless steel. The abrasive wear behaviour of the AISI 316 stainless steel surfaces coated with Fe-Cr-C and with 10 wt.-%, 15 wt.-%, 20 wt.-%, and 25 wt.-% B4C was investigated by using four loads and four distances for the 220 mesh SiC abrasive. Results were analyzed by variance analysis using ANOVA, and effects of parameters on the wear rate were determined as percentage rate. Furthermore, the error ratio was statistically evaluated. The experimental results were analyzed by the respective analysis of means and variance which is discussed in detail.
Keywords: Materials testing; Taguchi procedure; plasma transferred arc cladding; B4C